A TRPM7 mutation linked to familial trigeminal neuralgia: Omega current and hyperexcitability of trigeminal ganglion neurons - Gualdani, Roberta; Gailly, Philippe; Yuan, Jun-Hui; Yerna, Xavier; Di Stefano, Giulia; Truini, Andrea; Cruccu, Giorgio; Dib-Hajj, Sulayman D.; Waxman, Stephen G. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Trigeminal neuralgia (TN) is a unique pain disorder characterized by intense paroxysmal facial pain within areas innervated by the trigeminal nerve. Although most cases of TN are sporadic, familial clusters of TN suggest that genetic factors may contribute to this disorder. Whole-exome sequencing in patients with TN reporting positive family history demonstrated a spectrum of variants of ion channels including TRP channels. Here, we used patch-clamp analysis and Ca2+ and Na⁺ imaging to assess a rare variant in the TRPM7 channel, p.Ala931Thr, within transmembrane domain 3, identified in a man suffering from unilateral TN. We showed that A931T produced an abnormal inward current carried by Na⁺ and insensitive to the pore blocker Gd3+. Hypothesizing that replacement of the hydrophobic alanine at position 931 with the more polar threonine destabilizes a hydrophobic ring, near the voltage sensor domain, we performed alanine substitutions of F971 and W972 and obtained results suggesting a role of A931-W972 hydrophobic interaction in S3-S4 hydrophobic cleft stability. Finally, we transfected trigeminal ganglion neurons with A931T channels and observed that expression of this TRPM7 variant lowers current threshold and resting membrane potential, and increases evoked firing activity in TG neurons. Our results support the notion that the TRPM7-A931T mutation located in the S3 segment at the interface with the transmembrane region S4, generates an omega current that carries Na⁺ influx in physiological conditions. A931T produces hyperexcitability and a sustained Na⁺ influx in trigeminal ganglion neurons that may underlie pain in this kindred with trigeminal neuralgia.